Maximizing signal to leakage ratios in MIMO BCH cooperative beamforming scheme - Mohammed Fadhil; Nor Fadzilah Abdullah; Mahamod Ismail; Rosdiadee Nordin; Cebrail Ciftlikli; Musaab Al-Obaidi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Beamforming (BF) technique in cooperative multiple input multiple output (MIMO) antenna arrays improves signal to noise ratio (SNR) of the intended user. The challenge is to design transmit beamforming vectors for every user while limiting the co-channel interference (CCI) from other users. In this paper, we proposed cooperative beamforming based on Signal-to-Leakage Ratio (SLR) to exploit the leakage power as a useful power in the second time slot after user cooperation, for this purpose successive interference cancellation (SIC) is employed in each user to separate the leakage signal from the desired signal. Without increasing the complexity, Maximizing Signal-to-Leakage Ratio (SLR) subject to proposed power constraint instead of a unity norm is the way to achieve extra leakage power. To reduce the erroneous, Bose–Chaudhuri–Hocquenghem (BCH) codes employed in Beamforming of (SIC) cooperative scheme BF(CS-SIC-BCH). Maximum-likelihood (ML) estimator method is used at each user receiver. Simulation results show that the performance of the proposed scheme BF (CS-SIC-BCH) over Rayleigh and Rician fading channel is significantly better than the performance beamforming based on SLR in Non-cooperative system. More specifically to achieve a BER of about the required SNR for the proposed scheme is about 1 dB less than the Non-cooperative system.